2015
DOI: 10.1108/ajim-11-2014-0152
|View full text |Cite
|
Sign up to set email alerts
|

Altmetrics for the humanities

Abstract: Purpose – The purpose of this paper is to assess the value of Goodreads reader ratings for measuring the wider impact of scholarly books published in the field of History. Design/methodology/approach – Book titles were extracted from the reference lists of articles that appeared in 604 history journals indexed in Scopus (2007-2011). The titles were cleaned and matched with WorldCat.org (for publisher information) as well as Goodreads (for reader ratings) using an API. A set of 8,538 books was first filter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 28 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Because the site contains millions of user reviews of books, it may also inform librarians for purchasing strategies and other services (Blackwell & Springer, ; Herther, ; Hooper, ; Jeffries, ; Moyer, ; Naik, ; Stover, ; Tarulli & Caplinger, ; Wyatt, ). Some of the reviews and recommendations are of academic books and so the site may also be useful as a source of evidence about the impact of scholarly books (Zuccala, Verleysen, & Engels, ; Zuccala, Verleysen, Cornacchia, & Engels, ). Nevertheless, the commercial value of the site to publishers and its open nature gives it the potential to be spammed by fake positive reviews, as has been a problem on the http://Amazon.com site (BBC, ).…”
Section: Goodreadsmentioning
confidence: 99%
“…Because the site contains millions of user reviews of books, it may also inform librarians for purchasing strategies and other services (Blackwell & Springer, ; Herther, ; Hooper, ; Jeffries, ; Moyer, ; Naik, ; Stover, ; Tarulli & Caplinger, ; Wyatt, ). Some of the reviews and recommendations are of academic books and so the site may also be useful as a source of evidence about the impact of scholarly books (Zuccala, Verleysen, & Engels, ; Zuccala, Verleysen, Cornacchia, & Engels, ). Nevertheless, the commercial value of the site to publishers and its open nature gives it the potential to be spammed by fake positive reviews, as has been a problem on the http://Amazon.com site (BBC, ).…”
Section: Goodreadsmentioning
confidence: 99%
“…Reviews are also one of the most characteristic footprints of a book, and the data originating from tools such as Amazon and Goodreads are certainly of crucial importance as has already been reported in prior studies (Zuccala and Van Leeuwen, 2011;Gorraiz et al, 2014b;Zuccala et al, 2015). More than half of the books were "captured" in Goodreads while only one-fourth in Mendeley.…”
Section: Indicators Analysismentioning
confidence: 86%
“…• library holdings such as the number of catalog entries per book title in WorldCat ® (Torres-Salinas and Moed, 2009), library bindings (Linmans, 2010), and even introducing an indicator of perceived cultural benefit (White et al, 2009) • document delivery requests (Gorraiz and Schlögl, 2006) • library loans (Cabezas-Clavijo et al, 2013) • publishers' prestige (Torres-Salinas et al, 2012, 2013Giménez-Toledo et al, 2013) • book reviews (Nicolaisen, 2002;Zuccala and Van Leeuwen, 2011;Gorraiz et al, 2014b;Bornmann, 2015;Kousha and Thelwall, 2015a,b;Zuccala et al, 2015;Kousha et al, 2016;Thelwall and Kousha, 2016;Zhou et al, 2016) • altmetrics (Zhou and Zhang, 2013).…”
mentioning
confidence: 99%
“…It can directly reflect the degree of academic outputs concerned or used. The earliest empirical analysis of book impact using altmetric indicators was by Zuccala et al (2015), who took 8,538 books published in the field of history as their study sample and found a weak correlation between citation counts and Goodreads reader rating counts. Kousha and Thelwall (2016b) found a low-to-moderate correlation between citations and Amazon reviews based on a set of 2,739 academic books and a set of 1,305 bestsellers.…”
Section: Literature Reviewmentioning
confidence: 99%